The Comprehensive Evaluation of the National Higher Education System Based on EWM and ARMA Models. (26th April 2021) - Xu, Li-Jun; Liang, Yan; Su, Jin-Tao; Ouyang, Tong; Zhu, Jia-Ming
Abstract : Different countries have different education systems and their advantages and disadvantages. It is necessary to optimize their own higher education system and formulate policy plans to fully realize the optimization of the higher education system. For this reason, we propose to establish a continuous evaluation model of higher education health. This study mainly uses principal component analysis (PCA) and entropy weight method (EWM) to determine the evaluation model of higher education health status and makes autoregressive moving average model (ARMA) time series analysis based on the higher education evaluation model, which is obtained by studying long-term trends. The future development of education realizes the evaluation of sustainability. For Vietnam, that needs to be adjusted, the evaluation indicators based on the health status of the higher education system in developing countries will be added, tested, and adjusted and combined with the ARMA model prediction to determine the time period for the policy to meet reasonable expectations, and targeted development policies are proposed. Finally, we test the sensitivity of the established model, evaluate and analyze the advantages and disadvantages of the model, And combine the full text analysis to get the final conclusion.